Obstacles Facing Health Sector Workers, Especially Nursing - Tasnim Ahmed Hosein; Sara Mahdi Al Dilh; Mona Atiyah Almehmadi; Fatimah Hussain Mutaen; Eman Albeladi; Nada Abdullah Almontasheri; Maryam Hassan Atwani; Sara Aleryani; Mesfer Mohammed Alasmari; Saad Mohammed Al Ashgan (International Journal of Medical Toxicology and Legal Medicine, 2023)
1. Introduction The challenges that are posed to healthcare workers directly impact the level of care that is available to patients; the short- and long-term consequences of these challenges largely overlap and intertwine in complex ways. Moreover, the various challenges that healthcare workers face transcend any simple comparison by location, gender, or specific health worker profession. Many health workers find themselves demotivated by their difficult circumstances and are seriously contemplating leaving their jobs, which represents no small matter for an already weakened and struggling healthcare system. Each individual health worker, however, nevertheless attempts to deliver care of one kind or another despite the mounting and significant obstacles to achieving this crucial goal. Patients within the healthcare sector deserve greater recognition for their vital role in and the treatment they receive from the largest health worker population. Nurses, who are often seen as the overlooked backbone of the healthcare sector, occupy a unique and largely unjustified position at the periphery of the solutions that are proposed. These solutions are, nonetheless, presented in a manner reminiscent of an MBA-style approach – emphasizing “the critical need to invest in healthcare staff – urgently and comprehensively across the board.” 2 methods Research has shown that understanding the challenges facing health workers requires a broad view of the needs and expectations of health workers, taking into consideration all the spheres of health worker motivation and the work atmosphere in which they operate. On the macro level, recent analysis showed that an urgent need exists to invest in health worker wages, provide better access to training opportunities, and increase the population-to-doctor ratio in Although salaries were generally low, balancing them against cost-of-living indices yielded a different picture. Most health workers earned salaries clearly above the relative income that would be necessary to cover basic needs. Substantial income inequalities existed between rural and urban regions and between private and public facilities. Overall, a great deal of goodwill, dedication, and belief in a just cause was necessary for health workers to function in such environments. conclusion Currently, the health sector is facing a range of challenges. The limited time to give adequate care to each patient is coupled with multiple patients, insufficient resources, lack of receiving the right supplies as requested, lack of money to acquire the demanded supplies, lack of collaboration and communication among departments, understaffing, and a limited number of health workers were considered as challenges for patient care. The need to consult other departments for advanced diagnoses, organizations of drugs and supplies, and workloads assigned to health workers in other departments were considered as challenges for health care workers. Thus, the lack of and masking by professional training, low income, poor transport system, lack of rewards, lack of recognition by the higher authority, and prohibitions from public health departments were considered as challenges related to the profession itself and management and organizational level 1. The shortage of supplies and drugs assigned in this regard and having the vaccines and treatment standards were considered as challenges for the health system. The effect of the supportive supervision on health care involvement and gradually. On the responders’ quality of life, the loading factor of each variable was greater than 0.4 in generation of factors and greater than 1.5 in rotation. During the qualitative data collection with focus group discussions, the valid points which were not adequately addressed in the questionnaire were noted.